Comparison of Different Warfarin Reversal Protocols on Surgical Delay and Complication Rate in Hip Fracture Patients. (August 2013) - Leonidou, Andreas; Rallan, Rishi; Cox, Nancy; Pagkalos, Joseph; Luscombe, Jonathan
Purpose: To compare the effects of different warfarin reversal protocols on surgical delay and complication rate in hip fracture patients. Methods: Records of 7 men and 17 women aged 68 to 93 (mean, 82) years who were on warfarin and underwent surgery for femoral neck fractures were reviewed. The time to surgery, complication rate, and mortality were recorded, as were the International Normalised Ratio (INR) on admission and the day of operation, as well as the dose, route, and time of administration of vitamin K for reversing the anticoagulation effect of warfarin. Patients were divided into 4 groups based on the warfarin reversal treatment. Group 1 (n=4) included patients who did not receive reversal treatment, as their admission INR was ≤1.5. Group 2 (n=6) included patients who did not receive reversal treatment even though their INR was >1.6. Group 3 (n=5) included patients who received inappropriate reversal treatment (late or low-dose oral administration). Group 4 (n=9) included patients who received appropriate reversal treatment in terms of dose, route, and time of administration. Results: Among the 4 groups, the mean INR was 2.2 (range, 1.3–4.6) on admission and 1.4 (range, 1.0–1.6) on the day of surgery. Group 1 was excluded from further analysis. Respectively in groups 2, 3, and 4, the mean times to surgery were 2.3, 2.6, and 1.2 days, and the complication rates were 67%, 20%, and 11%. Conclusion: Early administration of intravenous vitamin K for hip fracture patients on warfarin is recommended to ensure early operative management and avoid postoperative complications.